The cognitive dissonance of poetic image in Ghazal - Muslim, Umalbaneen; Mohee, Inaam (Al-Adab Journal, 2023)
This paper describes one of the approaches to the concept of cognitive dissonance in the graphic image, which is related to the subject of Ghazal. the words of ugliness, incompatibility, became common, and the paper began by presenting the opinions of critics in disharmony and its patterns, then explaining the reasons leading to the disharmony of Ghazal images and the different tastes in them based on the different environments and era, and how the image that lacked harmony with its parts creates a gap between them and the reader, the criticism sought bridge by modifying the text in a way that elevates its pictorial level to the rank of art based on proportionality and harmony, taking into account the factors controlling taste and guiding readers to receive the pictorial language of poetry.